Self-care in pregnancy and breastfeeding: views of women and community pharmacists in Thailand - Boonyaprapa, Sathon (2010)
During pregnancy and breastfeeding, women are concerned about the health and safety of themselves and their baby. They undertake many activities in order to maintain good health, manage minor ailments and improve their lifestyle, including seeking help and advice from pharmacies. Community pharmacists have an important role in selecting appropriate medicines and encouraging good health behaviours. The Thai population can purchase medicines from pharmacies without a prescription, and self-treatment or self-medication is commonly used and important to the health status of Thai people. In addition, culture, family and relatives have an influence on health behaviours in Thailand. There have been very few previous studies about self-care behaviours including self-medication in Thailand focused on healthy women during pregnancy and breastfeeding, and the views of community pharmacists in self-medication and self-care during pregnancy and breastfeeding. In addition, the modern lifestyle and accessible health information might be affected by the current attitudes and behaviours of women during pregnancy and breastfeeding. Therefore, an investigation of self-care behaviours in pregnant and breastfeeding women was needed to explore their recent behaviours in terms of maintaining health and well-being as well as managing minor ailments. Views and experiences of community pharmacists about self-care in pregnancy and breastfeeding were also explored. This study contributes to the understanding of self-care behaviours and indicates the actual situation in community pharmacies regarding self-care and self-medication in pregnancy and breastfeeding. Two in-depth interviews in the Thai language were held with 43 women in Chiangmai about their self-care experiences and behaviours during pregnancy (>34-weeks gestation) and 35 out of the 43 women in the breastfeeding period (>four weeks following birth). Audio-taped interviews were transcribed, translated and analysed by using interpretative analysis. In addition, a postal questionnaire survey was used to collect data from 198 full-time community pharmacists in Chiangmai province. The first mailing was sent in April 2006 and a reminder was posted in June 2006. The completed questionnaires were returned from 110 pharmacists and the response rate was 56%. The majority of pregnant women tended to change their habits and adopt activities that they thought could make them and their babies healthy. They tried to consult their doctor rather than self-medicating. The traditional beliefs still had a very strong influence on most women interviewed during both pregnancy and postnatal period. The majority of pharmacists strongly agreed that self-care is important for both pregnant and breastfeeding women and they believed they provided good support for these women. Some pharmacists, however, still lacked the confidence to provide appropriate advice for these women and appeared to need more support with up-to-date information. Regarding the implications of this study, some self-care activities are harmful to women and their babies, so their dangers should be widely advertised in appropriate places. Furthermore, health professionals should consider a balance between safe traditional beliefs and modern health systems to ensure the best self-care practices for both women and their babies. In addition, continuing education and up-to-date information will help to increase the pharmacists’ confidence in providing appropriate advice to pregnant and breastfeeding women.